2010
DOI: 10.1901/jeab.2010.94-125
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Emergence of Behavioral Control by Underselected Stimuli in Humans After Reduction of Control by Overselected Stimuli

Abstract: Stimulus overselectivity occurs when only one of potentially many aspects of the environment controls behavior. Adult participants were trained and tested on a trial-and-error discrimination learning task while engaging in a concurrent load task, and overselectivity emerged. When responding to the overselected stimulus was reduced by reinforcing a novel stimulus in the presence of the previously overselected stimulus in a second trial-and-error discrimination task, behavioral control by the underselected stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…However, as the opportunities to pay due attention to both elements of the compound increase (either because of the lack of cognitive load or because of the increased stimulus duration), the over-selectivity effect disappears. However, the findings of retrospective revaluation in Experiments 2 and 3 entirely discredit the attention deficit perspective because in order for the initially under-selected stimulus to re-emerge and Running Head: STIMULUS OVER-SELECTIVITY AND CS DURATION control behaviour, it would have had to have been attended to in initial training (see also Broomfield et al, 2010). Alternatively, the findings can be accounted for by a variant of the comparator hypothesis (e.g., Denniston, et al, 2001;Matzel et al, 1985;Miller & Matzel, 1988;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the opportunities to pay due attention to both elements of the compound increase (either because of the lack of cognitive load or because of the increased stimulus duration), the over-selectivity effect disappears. However, the findings of retrospective revaluation in Experiments 2 and 3 entirely discredit the attention deficit perspective because in order for the initially under-selected stimulus to re-emerge and Running Head: STIMULUS OVER-SELECTIVITY AND CS DURATION control behaviour, it would have had to have been attended to in initial training (see also Broomfield et al, 2010). Alternatively, the findings can be accounted for by a variant of the comparator hypothesis (e.g., Denniston, et al, 2001;Matzel et al, 1985;Miller & Matzel, 1988;.…”
Section: Discussionmentioning
confidence: 99%
“…The over-selectivity effect is observed across many disabilities, including Autism Spectrum Disorders (ASD; Hedbring & Newsom, 1985;Koegel & Wilhelm, 1973;Lovaas & Schreibman, 1971;Schreibman & Lovaas, 1973), learning disabilities (Bailey, 1981;Gersten, 1983;Schneider & Salzberg, 1982;Wilhelm & Lovaas, 1976), acquired neurological damage (Wayland & Taplin, 1982, as well as in the elderly (Kelly, Leader, & Reed, 2016;McHugh & Reed, 2007). Over-selectivity has also been observed in intellectually typical adults undergoing high cognitive demands, or a concurrent and distracting activity (Broomfield, McHugh, & Reed, 2008a, 2008b2010;Reynolds & Reed, 2011a, 2011b.…”
mentioning
confidence: 99%
“…4 Mean percentage change from the test to the re-test phase for the most and least-selected stimuli in the experimental and control groups across the three age groups. Error bars = 95 % confidence intervals research exploring the effects of increased cognitive load on levels of over-selectivity in a non-clinical population (Broomfield et al 2010;Reed and Gibson 2005;Reynolds and Reed 2011a, b;Reynolds et al 2012). In addition, an age trend in over-selective responding emerged, where overselectivity increased as a function of chronological age.…”
Section: Discussionmentioning
confidence: 99%
“…This is the same distractor task used by Reed and Gibson (2005) and McHugh and Reed (2007). Previous research investigating over-selectivity in typically developing adults has demonstrated that adding a distractor task can induce higher levels of over-selective responding (Reed and Gibson 2005;Broomfield et al 2010;Reynolds et al 2012;Reynolds and Reed 2011a, b).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research (e.g., Broomfield, McHugh, & Reed, 2010;Leader, Loughnane, McMoreland, & Reed, 2009;Mchugh & Reed, 2007;Reed & Gibson, 2005;Reed et al, 2009;Reynolds & Reed, 2011a, 2011b has provided participants with verbal feedback (rather than points feedback) after selection of the stimuli, in the form of 'yes' or 'correct', for selecting the reinforced compound (e.g., AB), and 'no' or 'incorrect', for selecting the punished compound (e.g., CD). Research employing verbal feedback (e.g., Reynolds & Reed, 2011a, 2011b indicates less over-selectivity than the current research that utilizes a points based system.…”
Section: Methodsmentioning
confidence: 99%